The U.S. Constitution - Murray, Laura K., 1989- (2020)
"Encourage good citizenship and teach young readers about primary sources as they learn about the U.S. Constitution. Readers will get an inside look at the document on which our nation was founded, along with the branches of government, courts of law, amendments, and rights. Written at-level and with curriculum-based content, students will learn about the events leading up to the 1787 Constitutional Convention and how this important document still impacts America today."--Provided by publisher.
Includes bibliographical references (page 23) and index.
Grades K-3.
Ages 6-8.
Keywords: United States. -- Juvenile literature; United States -- Politics and government -- 1783-1789 -- Juvenile literature